A extrafiscalidade no ICMS: seletividade, essencialidade, neutralidade e efeito indutor das normas tributárias à luz da Constituição Federal de 1988 - Silva, Rafael Vega Possebon da (2015)
The present dissertation aims the analysis, from a legal standpoint, of the non-fiscal purposes of taxation related to the ICMS1, understood as the effects caused by the collection of this tax besides the generation of income to the State. Therefore, we start studying the economic effects of taxation, as well as the social and historical background that justifies tax imposition. From understanding that the tax phenomenon implies interdependence between the legal and social systems, we found that the positive law can assimilate those effects caused by taxation, in its relation to axioms that became part of the legal order through legal values, legal principles and programmatic guidelines printed in the Federal Constitution. A systematic and constitutional interpretation of tax legislation should, therefore, be alert to these direct and indirect implications of the exaction, in order build a coherent and cohesive legal system, having in mind the purpose of the State as determined by the Constitution. The non-fiscal purposes of taxation can be studied under several perspectives, among which the effects of the charging in relation to: (i) the distribution of the tax burden in an equitable and progressive way, in respect to equality and the ability to pay (distributive function); (ii) the fulfillment of constitutional values through behavior induction (allocative function); and (iii) its use as a tool to stabilize market flows, as an anti-cyclical policy (stabilizing function). The first two are subject to further analysis. Nonetheless, apart from the search for legal certainty, tax neutrality, as an autonomous legal principle that also represents a canon protected by the legal system, acts as a counterpoint that must be taken into consideration in every discussion related to non-fiscal tax effects. In light of these concepts, we analyze the ICMS tax, studying the particularities of this form of taxation and the application of the discussed notions to some selected situations. The principle of selectivity consists in a tool to guide the variation of the tax burden that will be applied together with certain specific criteria, depending on the protected constitutional value and the non-fiscal function pursued. Considering the ICMS as a tax on consumption, with relevant impact of such tax burden to the end consumer, we conclude that the selectivity based on the essentiality of products / services is mandatory in the ICMS, and enables the variation of the tax burden as a way to comply as far as possible with the search for the ability to pay of the end consumer. After all, we conclude that the current ICMS legislation conflicts with several axioms protected by the legal system, resulting in a violation of the Constitution. We understand that this violation can be subjected to judicial review, and so we seek to present some elements and objective parameters to guide the analysis of the law by the interpreter in such cases